PENGUATAN PEMASARAN BERBASIS DIGITAL DAN KOMUNITAS DI NU CARE LAZISNU KOTA SURAKARTA - Ivantri, Madha Adi; Marzuqi, Achmad Mufid; Faruk, Ahmad; Lestari, Asih Puji; Khoiriyah, Shofiatul (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
This community service aims to enhance digital and community-based marketing. Based on the situational analysis of the partner, NU Care LAZISNU Surakarta, this initiative is highly relevant considering the challenges faced and the development stage of the partner organization. The community service method employed at NU Care LAZISNU Surakarta uses an ABCD (Asset-Based Community Development) approach, where the service team encourages the partner to understand and utilize their potential and strengths. Technical steps, such as outreach and mentoring, are carried out in the marketing aspect. The outreach materials cover the importance of marketing communication in the digital era and community-based marketing for zakat management institutions. The community service team also provides guidance in managing websites and Instagram as tools for digital and community-based marketing to establish communication and transparency with community partners.